Beating Sony at its own game [copyright protection]. - Kushner, D. (IEEE spectrum)
This paper reports on how hackers are able to exploit the features of Sony's Playstation Portable (PSP) handheld gaming device to discover exciting, new applications. Sony's decision to add a Web browser to the PSP is actually an effort to counter the release of an unauthorized Web browser months before. Sony is now discovering that hackers are able to circumvent their copyright protection scheme to run home-brewed programs off the PSP's memory stick and hack into their proprietary media discs, which store PSP games and movies. To address these loopholes, Sony has turned to firmware to prevent gamers from playing home-made codes. While Sony recognizes the creativity of hackers in adding modifications to its products, the company has a rollout plan for the PSP ready and intends to diligently follow its schedule of official updates.